IMPLEMENTATION OF THINK, TALK, WRITE LEARNING MODEL TO IMPROVE STUDENTS SELF-CONFIDENCE AND LEARNING OUTCOMES - Ginting, Elisa Br; Ginting, Aladin F Tinus; Waruwu, Ermina (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Self-confidence is one of the most important things for students to have so they can participate in learning actively. Through the implementation of the Think, Talk, Write (TTW) model, it has great potential to improve self-confidence and student learning outcomes. Through critical thinking, collaborative discussions, and reflective writing, students can develop a deeper understanding of religious teachings and feel more confident in applying them in everyday life. However, despite its great potential, the application of the TTW model in the context of religious learning has not been widely researched, especially at the junior high school level and in the context of Catholic education. This study aims to improve self-confidence and student learning outcomes by using the Think, Talk, Write learning model for students of SMP Budi Murni 3 Medan. This study is a Classroom Action Research (CAR) involving 26 students of Phase D Grades VII-2 Academic Year 2024/2025. The methods used include: planning, implementation, observation, and reflection. Data collection uses observation, documentation, and assessment of test results that have been made in the form of multiple choices. The results show a significant increase in student self-confidence and learning outcomes by using the Think, Talk, Write model. Student self-confidence increased by 16.66%, and student learning outcomes improved by 22.7%. The Think, Talk, Write model has been proven to encourage student active learning, increase self-confidence, and improve student learning outcomes.